Effects of quantum medicine applied to paralympic athletics training on physical performance in Colombia - Montenegro-Collazo, Eduardo Víctor (Sport Science Training and Research, 2026)
Introduction: The training of Paralympic athletes requires innovative methods tailored to their specific physiological and neuromotor needs. In this regard, sports quantum medicine may emerge as a complementary strategy to improve physiological efficiency, neuromuscular recovery, and athletic performance, although scientific evidence in Paralympic populations remains scarce. Objective: To determine the effect of a quantum medicine program on aerobic capacity and physical performance in Paralympic athletes. Methodology: A quantitative, pre-experimental study was conducted on 48 Paralympic athletes from Colombia. The intervention lasted eight weeks, with 90-minute sessions five times per week. The program incorporated quantum bioenergetic stimulation, functional strength exercises, progressive sprints, and individualized running technique work. Maximum oxygen uptake (VO₂ max) and times in the 100 m, 200 m, 800 m, and 1500 m tests were measured using standardized protocols. Results: Statistically significant improvements were observed in all indicators studied: VO₂ max. (p = 0.0001), 100-m and 200-m sprint speed (p = 0.0001), and performance in the 800-m and 1500-m tests (p < 0.0002) in all participants. Discussion: The results indicate that quantum medicine integrated into adapted physical training can improve physiological and neuromuscular adaptation processes, maximizing aerobic and anaerobic performance in Paralympic athletes. Conclusions: Quantum medicine and individualized training significantly and durably improved aerobic capacity and physical performance, making it a promising complementary strategy in adapted sports training.